Analysis of the physical aspects of quality of life of kidney recipients - Ana Elza Oliveira de Mendonça; Marina de Góes Salvetti; Eulália Maria Chaves Maia; Ana Cristina de Oliveira e Silva; Gilson de Vasconcelos Torres (Revista da Escola de Enfermagem da USP, 2015)
OBJECTIVE To identify the main factors of the physical domain modified after kidney transplantation and analyze the influence of those aspects in the perception of Overall quality of life (QOL). METHOD Longitudinal study, conducted with 63 chronic kidney patients, evaluated before and after kidney transplant, using the quality of life scale proposed by the World Health Organization. RESULTS We observed significant improvement in the physical aspects of QOL after kidney transplantation. Significant correlations were observed between physical aspects and the Overall QOL. CONCLUSION The kidney transplant generated improvement in all physical aspects of QOL. The factors that showed stronger correlation with the Overall QOL before the transplant were the capacity to work and pain. After the transplant, the perception of need for treatment was the factor that showed stronger correlation with the Overall QOL.